Global Warming and Climate Change: What Australia knew and buried...then framed a new reality for the public - Taylor, Maria (ANU Press, 2014)
Relevant to both Australian and overseas audiences, here is the untold story of how Australia buried its knowledge on climate change science and response options during the 1990s - going from clarity to confusion and doubt after arguably leading the world in citizen understanding and a political will to act in the late 1980s.